2020
DOI: 10.1177/0022185620918623
|View full text |Cite
|
Sign up to set email alerts
|

From equal pay to overcoming undervaluation: The Australian National Pay Equity Coalition 1988–2011

Abstract: Australian feminists have struggled to define the International Labour Organisation’s Equal Remuneration Convention’ goal of gender pay equity and find a platform for achieving it. Approaches based on discrimination, or a male comparator, have proved unworkable. Networking nationally and internationally, the National Pay Equity Coalition (1988–2011) formulated many submissions to industrial tribunals and parliamentary inquiries. Early interventions argued the disadvantages to women of the decentralisation of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This approach was integrated into pay equity efforts despite the dynamic of gender dominance underlying job evaluation methods and despite critical discourse on HR practices as tools of power and domination that perpetuate the undervaluing of certain jobs, including home care (Townley, 1993). 3 In line with that critique, Deborah Figart (1997) states: “the lived experience of discrimination requires qualitative analysis, in order to trace the influence of labour market structures within broader gender systems of social organisation and power distribution” (Blackman et al, 1988: 587).…”
Section: History and Origin Of Job Evaluation Methodsmentioning
confidence: 99%
“…This approach was integrated into pay equity efforts despite the dynamic of gender dominance underlying job evaluation methods and despite critical discourse on HR practices as tools of power and domination that perpetuate the undervaluing of certain jobs, including home care (Townley, 1993). 3 In line with that critique, Deborah Figart (1997) states: “the lived experience of discrimination requires qualitative analysis, in order to trace the influence of labour market structures within broader gender systems of social organisation and power distribution” (Blackman et al, 1988: 587).…”
Section: History and Origin Of Job Evaluation Methodsmentioning
confidence: 99%
“…This particular challenge was addressed prominently and selflessly by Fran in her work for the National Pay Equity Coalition (NPEC), a feminist policy and advocacy group. The work of NPEC, together with other organisations, was ultimately prominent in analysing the gender pay gap not ‘in terms of differences between women and men, but in terms of the failure of classification structures, skill recognition systems and evaluation methods to give due weight to the demands of work done by women’ (Blackman et al, 2020: 601).…”
Section: Professor Meg Smith Western Sydney Universitymentioning
confidence: 99%
“…The two then continued to collaborate in the National Pay Equity Coalition (NPEC) convened by Meredith Burgmann and including Suzanne Hammond, Anne Junor and Meg Smith. A fine account of Fran's efforts in the struggle for pay equity can also be found in Anne Junor's Obituary, published in February 2024 in the Economic and Labour Relations Review (Junor, 2024) and further accounts can be found in Smith (2008), Blackman et al (2019) and Blackman et al (2020). It is important to acknowledge that Fran was one of the authors of the latter two articles, one of which appeared in the Journal of Industrial Relations .…”
mentioning
confidence: 99%
“…The experiences of Australia and New Zealand are further elaborated in two articles that address the impact of coalitions of activists in refining the concept of gender pay inequality and mobilising action to redress it. Blackman et al. (2020) provide an insider’s view of the ways in which the National Pay Equity Coalition (NPEC) in Australia promoted the goal of redressing the undervaluation of feminised work.…”
Section: Dissecting the Barriers: Insights From Australia New Zealanmentioning
confidence: 99%